Queratitis por Lasiodiplodia theobromae: comunicación de un caso y revisión de la literatura - Samudio, Margarita (2014)
We report a case of mycotic keratitis caused by Lasiodiplodia theobromae in a 60-year-old man with a history of ocular trauma with vegetable matter. Ophthalmological assessment with slit-lamp and microbiological evaluation of the corneal ulcer by conventional microbiological techniques were performed. Mycology study of the corneal scraping showed the presence of fungal filaments and the isolate was identified as Lasiodiplodia theobromae. Patient was treated with natamycin 5% and fluconazole 0.2% for 37 days. The infection was controlled but the corneal scars required a cornea transplant. This is the first case of keratitis by Lasiodiplodia theobromae in Paraguay. Difficulties in the management of these cases, which often requires surgical procedures, are discussed.